Selection of nutrients for the production of Myco-coagulant from Mycelial fungus fermentation - Hamidah, Hassan; Mamun, Abdullah Al; Alam, Md. Zahangir (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Despite potential negative effects on human health and other living beings, chemical coagulants are widely used for the removal of suspended solids and turbidity from water. Therefore, search for efficient bio-coagulants is still on going in various parts of the world. Myco-coagulant is successfully produced by a research team at the Bioenvironmental Engineering Research Centre (BERC) at IIUM. This study is being conducted as a continuation of the previous study where myco-coagulant was produced from locally isolated river water fungus (RWF), known as Lentinus squarrosulus. The myco-coagulant is applied in water treatment process to reduce the turbidity synthetic water prepared from kaolin suspension by performing flocculation mechanism. This paper is prepared to report the findings on the attempt to optimize the nutrients required for the proper growth and optimum production of the myco-coagulant from the fungus. The results obtained from the Plackett–Burman design indicated that the positive effect of yeast extract was most influential (11.17%) followed by malt extract (6%), inoculum size (3.5%) and glucose (3%). Agitation speed had the highest negative influence (-12.17) followed by urea (-7.67%), pH (5.83%, culture period (5.50%) and CaCl2 (5%). However, amount of yeast extract and agitation speed were considered to be the major factors for further optimization.